Determination of Willingness to Pay Compensation the Potential and Readiness of Accountants in Opinions of Entrepreneurs in era Thailand 4.0 - Pimpavee Maneewong,Supawadi Maneewong, Bundit Anuyahong, Wipanee Pengnate, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objective of this research aimed to1) study the factors affecting the determination of willingness to pay, and 2) study the willingness to pay compensation the potential and readiness of accountants in entrepreneurs. This research employed quantitative research. Samplesof this study were 693 entrepreneurs in Prachuap Khiri Khan Province. The stratified random sampling and hypothetical methods for evaluating events by using the Double Bounded CVM questionnaire were used in this study. The results of the study were: 1) Factors that affect the determination of willingness to pay compensation according to the potential and readiness of the accountants in the view of the entrepreneur, namely the characteristics of the business types, job characteristics and work ability, such as accounting professional knowledge,accounting information technology competency,and language ability; and 2) Entrepreneurs were willingness to pay an average starting at 12,090.39 baht per month, willingness to pay compensation when the workload increases from working in government agencies 1,052.11 baht per month,willingness to pay compensation when responsibilities increased by being registered as an account keeper 1,775.18 baht per month, willingness to pay compensation when the accountant's potential and readiness through the use of software packages for bookkeeping equal to 1,961.19 baht per month, and willingness to pay compensation when having English language ability of 2,643.24 baht per month. The results of this study reflected that the compensation that entrepreneurs who were willing to pay was less than the minimum wage. As a result of economic conditions,including the epidemic crisis of the corona virus 2019 infection, accountants were able to use this information to guide potential development and readiness in accordance with the needs of entrepreneurs including government agencies to determining the labor cost according to the scope of the study.